TEACHING COMPOSITION AND COLOR HARMONY TO STUDENTS USING DIGITAL TOOLS - Usmonov Umid Farxodovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: The integration of digital tools in art education provides innovative opportunities for teaching essential artistic concepts such as composition and color harmony. By using software applications, interactive platforms, and digital design programs, educators can offer students hands-on, visual, and engaging learning experiences. This study explores how digital technologies can enhance students’ understanding of compositional balance, color relationships, and aesthetic decision-making in art projects. It also examines pedagogical strategies for implementing digital tools in classrooms, highlights benefits for students’ creativity and visual literacy, and discusses potential challenges in technology-based art instruction.